A retrospective epidemiological study of type 1 diabetes mellitus in Wales, UK between 2008 and 2018. (2021) - Rafferty, James; Stephens, Jeffery W.; Atkinson, Mark D.; Luzio, Stephen D.; Akbari, Ashley; Gregory, John W.; Bain, Stephen; Thomas, Rebecca L.; Owens, David R.
No abstract available